Spherical cap harmonic analysis of the Arctic ionospheric TEC for one solar cycle. Issue 1 (30th January 2014) - Liu, Jingbin; Chen, Ruizhi; An, Jiachun; Wang, Zemin; Hyyppa, Juha
Abstract Precise knowledge of the Arctic ionosphere total electron content (TEC) and its variations has scientific relevance due to the unique characteristics of the polar ionosphere. Understanding the Arctic TEC is also important for precise positioning and navigation in the Arctic. This study utilized the spherical cap harmonic analysis (SCHA) method to map the Arctic TEC for the most recent solar cycle from 2000 to 2013 and analyzed the distributions and variations of the Arctic TEC at different temporal and spatial scales. Even with different ionosphere conditions during the solar cycle, the results showed that the existing International Global Navigation Satellite Systems Service stations are sufficient for mapping the Arctic TEC. The SCHA method provides adequate accuracy and resolution to analyze the spatiotemporal distributions and variations of the Arctic TEC under different ionosphere conditions and to track ionization patches in this polar region (e.g., the ionization event of 26 September 2011). The results derived from the SCHA model were compared to direct observations using the Super Dual Auroral Radar Network radar. The SCHA method is able to predict the TEC in the long and short terms. This paper presented a long‐term prediction with a relative uncertainty of 75% for a latency of one solar cycle and a short‐term prediction with errors of ±2.2 total electron content units (TECUs, 1 TECU = 1016 el m−2), ±3.8 TECU, and ±4.8 TECU for a latency of 1, 2, and 3 days, respectively. The SCHA is an effective method for mapping, predicting, and analyzing the Arctic TEC.